1996
DOI: 10.1097/00006123-199608000-00026
|View full text |Cite
|
Sign up to set email alerts
|

Release of γ-Aminobutyric Acid in the Dorsal Horn and Suppression of Tactile Allodynia by Spinal Cord Stimulation in Mononeuropathic Rats

Abstract: Our results indicate that the development of allodynia, a common symptom in neuropathic pain states, may be linked to a decreased spinal release of GABA. We suggest that an SCS-induced release of GABA could be important for the suppression of allodynia observed in rats after SCS. Similar mechanisms could also be involved in the SCS-induced alleviation of pain in patients with peripheral neuropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
186
3
9

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 290 publications
(205 citation statements)
references
References 39 publications
7
186
3
9
Order By: Relevance
“…28 It is of special interest that this effect on the GABA system occurred only in rats that in preceding experiments had been found to respond to SCS with significant suppression of hind paw hypersensitivity. 29 These results confirm earlier observations that the state of central hyperexcitability manifested in the development of allodynia after peripheral nerve injury relates to dysfunction of the spinal GABA systems, and it appears that SCS may act by restoring normal GABA levels in the dorsal horn. These findings were supplemented by behavioral experiments where we showed that that the allodynia-suppressive effect of SCS could be counteracted by intrathecal injection of a GABA B antagonist whereas the GABA A antagonist bicuculline was less effective.…”
Section: What Is Known About Transmitter Mechanisms Involved In Scs?supporting
confidence: 90%
“…28 It is of special interest that this effect on the GABA system occurred only in rats that in preceding experiments had been found to respond to SCS with significant suppression of hind paw hypersensitivity. 29 These results confirm earlier observations that the state of central hyperexcitability manifested in the development of allodynia after peripheral nerve injury relates to dysfunction of the spinal GABA systems, and it appears that SCS may act by restoring normal GABA levels in the dorsal horn. These findings were supplemented by behavioral experiments where we showed that that the allodynia-suppressive effect of SCS could be counteracted by intrathecal injection of a GABA B antagonist whereas the GABA A antagonist bicuculline was less effective.…”
Section: What Is Known About Transmitter Mechanisms Involved In Scs?supporting
confidence: 90%
“…The current study also shows that blockade of GABA A receptors in the spinal cord prevents the antihyperalgesia produced by high frequency TENS. Similarly, prior studies show increased extracellular concentrations of GABA in the spinal cord during dorsal column stimulation, at high frequency, also begins after removal of the stimulation and utilizes GABA receptors in the spinal cord to produce analgesia (Linderoth et al, 1994;Stiller et al, 1996). Dorsal column stimulation, delivered at sensory intensity and high frequency, would activate large diameter afferent fibers similar to TENS delivered at sensory intensity and high frequency .…”
Section: Gaba and High Frequency Tensmentioning
confidence: 80%
“…Supraspinal activation of mu-opioid receptors increases release of GABA in the spinal cord that is prevented by 5-HT 3 receptor antagonists (Kawamata et al, 2002). Indeed, dorsal column stimulation at high frequency (100 Hz), which would activate large diameter sensory afferents like TENS, also increases spinal release of GABA in normal animals and those with nerve injury (Linderoth et al, 1994;Stiller et al, 1996), and reduces glutamate release through activation of GABA B receptors (Cui et al, 1997). These data suggest that analgesia mediated by supraspinal μ-opioid receptors releases serotonin in the spinal cord that in turn activates 5-HT 3 receptors on GABAergic neurons resulting in release of GABA.…”
Section: Introductionmentioning
confidence: 99%
“…Activity-dependent central sensitization (heterosynaptic facilitation) is evident within seconds of a nociceptive conditioning stimulus and can outlast the stimulus for hours (Woolf and Wall, 1986). Within the dorsal horn, increases in excitatory amino acid concentrations (Somers et al, 2002) and reduction of GABA concentrations (Ibuki et al, 1997;Stiller et al, 1996) may also contribute to allodynia and hyperalgesia after nerve injury. The present results also suggest that upregulated expression of Na v 1.3 contributes to hyperresponsiveness of these central neurons after nerve injury.…”
Section: Discussionmentioning
confidence: 99%